2010
DOI: 10.1007/s10620-010-1383-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult Patients with Eosinophilic Esophagitis Do Not Show an Increased Frequency of the HLA-DQ2/DQ8 Genotypes Predisposing to Celiac Disease

Abstract: Our work does not allow us to establish a common genetic basis for EoE and CD because an increased frequency of the HLA DQ2 and DQ8 alleles predisposing to CD was not observed in adult EoE patients compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
0
28
0
2
Order By: Relevance
“…24 Similarly, a study by Lucendo and colleagues did not find increased HLA DQ2 and DQ8 (implicated in patients with celiac disease) in subjects with EoE when compared to controls. 35 Thus, the literature on this topic has been contradictory and confusing, likely because of variable study designs, inclusion criteria, and comparator groups, as well as relatively small sample sizes. It is not surprising that a recent systematic review examining the association between EoE and celiac disease found no clear association between the two conditions and concluded that there was a lack of robust studies for summarizing the realtionship.…”
Section: Discussionmentioning
confidence: 99%
“…24 Similarly, a study by Lucendo and colleagues did not find increased HLA DQ2 and DQ8 (implicated in patients with celiac disease) in subjects with EoE when compared to controls. 35 Thus, the literature on this topic has been contradictory and confusing, likely because of variable study designs, inclusion criteria, and comparator groups, as well as relatively small sample sizes. It is not surprising that a recent systematic review examining the association between EoE and celiac disease found no clear association between the two conditions and concluded that there was a lack of robust studies for summarizing the realtionship.…”
Section: Discussionmentioning
confidence: 99%
“…In another Australian study published in 2010 [24], the prevalence of esophageal eosinophilia in children with celiac disease who had concurrent esophageal biopsies was 8.2% (10 of 121), 60% males, 30% had normal-appearing esophageal mucosa at endoscopy; children who had undergone repeated endoscopic examinations showed recovery of duodenal mucosa but no resolution of esophageal eosinophilia on a gluten-free diet alone. The association of celiac and eosinophilic esophagitis may not be a true association but a matter of biased enrollment in the above studies: regarding HLA DQ2 and/or DQ8, a study [25] showed that these alleles were not present in eosinophilic esophagitis at a greater rate than in healthy controls. But a recent study [26] demonstrated, a clear association between celiac disease and eosinophilic esophagitis in both pediatric and adult populations: the standardized incidence ratio of eosinophilic esophagitis in patients with celiac disease was 16.0 (95% CI, 8.7–25.5).…”
Section: Resultsmentioning
confidence: 99%
“…In CD, genetic predisposition is related to the presence of HLADQ2 and, to a lesser extent, to HLADQ8. However, the prevalence of those alleles in patients with EoE does not seem to be higher than in the general population, and no polymorphism suggesting a common genetic basis between EoE and CD was identified yet 10. As for environmental factors, both diseases appear to share a component of aberrant immune response to ingested antigens and a response to dietary restrictions.…”
Section: Discussionmentioning
confidence: 95%